Combustion-resistant thermoplastic composition
Patent Information
- Application Number
- KR1020247015871
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-10-21
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-10-21
Smart Images

Figure 112024051656991-PCT00001 
Figure 112024051656991-PCT00002 
Figure 112024051656991-PCT00003
Abstract
Description
Technology Field
[0001] The present disclosure relates to a burning-resistant thermoplastic composition. The present disclosure also relates to the use of a lignin-based filler to improve the burning resistance of the thermoplastic composition. Furthermore, the present disclosure relates to a method for producing a burning-resistant thermoplastic composition. Additionally, the present disclosure relates to articles and uses of a burning-resistant thermoplastic composition. Background Technology
[0002] From the perspective of sustainability and the circular economy, it is desirable to use bio-based materials in applications such as thermoplastic compositions and packaging materials. The thermal stability of thermoplastic compositions is also an important characteristic for processing these materials. The goal is to provide environmentally friendly solutions regarding thermoplastic compositions. The problem to be solved
[0003] A flame-retardant thermoplastic composition is disclosed. The flame-retardant thermoplastic composition comprises at least one polymer and a lignin-based filler, the lignin-based filler is prepared from a lignin material that has undergone hydrothermal carbonization treatment, the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight, the burning rate of the flame-retardant thermoplastic composition is at least 20% lower than the burning rate of a corresponding thermoplastic composition, and the corresponding thermoplastic composition is prepared in a manner similar to the flame-retardant thermoplastic composition, but the lignin material used to prepare the lignin-based filler is not hydrothermal carbonized. means of solving the problem
[0004] In addition, the use of a lignin-based filler to improve the flame resistance of a thermoplastic composition is disclosed. The flame-resistant thermoplastic composition comprises at least one polymer and a lignin-based filler, the lignin-based filler is prepared from a hydrothermal carbonized lignin material, the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight, the combustion rate of the flame-resistant thermoplastic composition is at least 20% lower than the combustion rate of a corresponding thermoplastic composition, and the corresponding thermoplastic composition is prepared in a manner similar to that of the flame-resistant thermoplastic composition, but the lignin material used to prepare the lignin-based filler is not hydrothermal carbonized.
[0005] Additionally, a method for producing a flame-retardant thermoplastic composition comprising at least one polymer and a lignin-based filler is disclosed, comprising the following steps:
[0006] - A step of providing at least one polymer and a lignin-based filler, wherein the lignin-based filler is prepared from hydrothermal carbonized lignin, and the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight; and
[0007] - A step of forming a flame-retardant thermoplastic composition by combining at least one polymer and a lignin-based filler,
[0008] The combustion rate of the combustion-resistant thermoplastic composition is at least 20% lower than the combustion rate of the corresponding thermoplastic composition, and the corresponding thermoplastic composition is manufactured in a manner similar to that of the combustion-resistant thermoplastic composition, but the lignin material used to manufacture the lignin-based filler is not hydrothermal carbonized.
[0009] Additionally, articles comprising a flame-retardant thermoplastic composition as defined in the present specification are disclosed.
[0010] In addition, the use of a thermoplastic composition as defined in this specification is disclosed in packaging, housing, automotive parts, aviation parts, marine parts, machine parts, sports equipment, sports equipment parts, leisure equipment, leisure equipment parts, tools, tool parts, pipes, membranes, tubes, fittings, bottles, films, bags, sacks, textiles, ropes, containers, tanks, electrical parts, electronic parts, parts for energy generation, toys, home appliances, kitchenware, tableware, flooring, fabrics, medical applications, food contact materials, building materials, drinking water applications, and / or furniture. Specific details for implementing the invention
[0011] A flame-retardant thermoplastic composition is disclosed. The flame-retardant thermoplastic composition comprises at least one polymer and a lignin-based filler, wherein the lignin-based filler is prepared from a lignin material that has been hydrothermally carbonized, and the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight, and the combustion rate of the flame-retardant thermoplastic composition is at least 20% lower than the combustion rate of a corresponding thermoplastic composition, and the corresponding thermoplastic composition is prepared in a manner similar to that of the flame-retardant thermoplastic composition, but the lignin material used to prepare the lignin-based filler is not hydrothermally carbonized.
[0012] In addition, the use of a lignin-based filler to improve the flame resistance of a thermoplastic composition is disclosed. The flame-resistant thermoplastic composition comprises at least one polymer and a lignin-based filler, the lignin-based filler is manufactured from a hydrothermal carbonized lignin material, the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight, the combustion rate of the flame-resistant thermoplastic composition is at least 20% lower than the combustion rate of a corresponding thermoplastic composition, and the corresponding thermoplastic composition is manufactured in a manner similar to that of the flame-resistant thermoplastic composition, but the lignin material used to manufacture the lignin-based filler is not hydrothermal carbonized.
[0013] Additionally, a method for preparing a flame-retardant thermoplastic composition comprising at least one polymer and a lignin-based filler is disclosed, comprising the following steps:
[0014] - A step of providing at least one polymer and a lignin-based filler, wherein the lignin-based filler is prepared from hydrothermal carbonized lignin, and the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight; and
[0015] - A step of forming a flame-retardant thermoplastic composition by combining at least one polymer and a lignin-based filler,
[0016] The combustion rate of the combustion-resistant thermoplastic composition is at least 20% lower than the combustion rate of the corresponding thermoplastic composition, and the corresponding thermoplastic composition is manufactured in a manner similar to that of the combustion-resistant thermoplastic composition, but the lignin material used in the manufacture of the lignin-based filler is not hydrothermal carbonized.
[0017] Additionally, articles comprising a thermoplastic composition as defined herein are disclosed. In one embodiment, the thermoplastic composition is formed into an article by extrusion, injection molding, compression molding, blow molding, injection blow molding, injection stretch blow molding, thermoforming, vacuum forming, melt spinning, electrospinning, melt blowing, film blowing, film casting, extrusion coating, rotational molding, coextrusion, laminating, calendering, fused deposition modeling, or any combination thereof.
[0018] In addition, the use of a thermoplastic composition as defined herein is disclosed in packaging materials, housings, automotive parts, aviation parts, marine parts, machine parts, sports equipment, sports equipment parts, leisure equipment, leisure equipment parts, tools, tool parts, pipes, membranes, tubes, fittings, bottles, films, bags, colors, fabrics, ropes, containers, tanks, electrical parts, electronic parts, energy generation parts, toys, home appliances, kitchenware, tableware, flooring, cloth, medical products, food contact materials, building materials, drinking water products and / or furniture.
[0019] Therefore, the term "corresponding thermoplastic composition" should be understood to refer to a thermoplastic composition manufactured in a manner similar to that of a flame-retardant thermoplastic composition, but in which hydrothermal carbonization treatment is not used to manufacture lignin-based fillers. That is, all other components, their amounts, and process steps used to manufacture the corresponding thermoplastic composition remain the same as when manufacturing the flame-retardant thermoplastic composition, but the step of using hydrothermal carbonization treatment of lignin material is omitted when manufacturing lignin-based fillers for the corresponding thermoplastic composition.
[0020] Combustion rate can be measured according to standard ISO 3795:1989 (Road vehicles, and agricultural and forestry tractors and machinery - Measurement of combustion behavior of internal materials (horizontal combustion test); conditioning: 23°C and 50% relative humidity (RH)., sample size: 147 mm × 100 mm × 2 mm).
[0021] In one embodiment, the combustion rate of the flame-retardant thermoplastic composition is at least 30%, at least 40%, at least 50%, at least 60%, or at least 70% lower than the combustion rate of the corresponding thermoplastic composition.
[0022] The thermoplastic composition may contain 0.1-65 wt%, 0.3-60 wt%, 0.5-50 wt%, 1-40 wt%, 1.2-30 wt%, 1.5-20 wt%, 2-10 wt%, or 2.5-5 wt% of a lignin-based filler based on the total weight of the flame-retardant thermoplastic composition. In one embodiment, the flame-retardant thermoplastic composition contains a total amount of 0.1-60 wt%, 0.5-50 wt%, or 1-45 wt% of a lignin-based filler based on the total weight of the flame-retardant thermoplastic composition.
[0023] In this specification, "total weight" should be understood as the weight of all components of a flame-retardant thermoplastic composition containing possible moisture, unless otherwise specified.
[0024] A thermoplastic composition, or what may also be called a thermosoftening plastic composition, is a plastic polymer material that becomes flexible or moldable at a predetermined temperature and solidifies upon cooling.
[0025] The thermoplastic composition may be prepared using at least one polymer and a lignin-based filler. In the thermoplastic composition, at least one polymer and the lignin-based filler may be mixed together but may not react with each other. Additional components or materials, such as additives, lubricants, stabilizers, antioxidants, and other fillers, may also be used to prepare the thermoplastic composition.
[0026] In one embodiment, the step of combining at least one polymer and a lignin-based filler comprises preparing a masterbatch and then combining the polymer and the lignin-based filler. In one embodiment, the step of combining at least one polymer and a lignin-based filler comprises combining at least one polymer, a lignin-based filler, and an additive, and molding the formed flame-retardant thermoplastic composition. In one embodiment, the step of combining at least one polymer and a lignin-based filler comprises directly combining at least one polymer and a lignin-based filler under a processing temperature suitable for each polymer type. The processing temperature is elevated and is defined by the polymer supplier for each polymer.
[0027] When manufacturing a flame-retardant thermoplastic composition, a so-called masterbatch can first be prepared using a polymer and a lignin-based filler. The masterbatch can be prepared by mixing the polymer and the lignin-based filler at elevated temperatures. Additionally, other additives, lubricants, stabilizers, antioxidants, and other fillers may be included in the masterbatch as needed. A masterbatch is generally considered to be a solid product (typically a plastic, rubber, or elastomer) in which pigments or fillers are optimally dispersed at high concentrations in a carrier material. The carrier material is compatible with the main plastic to be mixed during molding, so that the final plastic product, i.e., the thermoplastic composition, obtains its color or properties from the masterbatch.
[0028] Alternatively, the thermoplastic composition is directly blended from the polymer and the lignin-based filler at elevated temperatures. Additionally, other additives, lubricants, stabilizers, antioxidants, and other fillers may be directly blended with the polymer and the lignin-based filler as needed.
[0029] The temperature used when combining at least one polymer with a lignin-based filler may vary depending on the type of polymer used. Suitable temperatures for each polymer are readily available to those skilled in the art. Additionally, polymer suppliers define suitable processing temperatures for different polymers. Generally, temperatures of, for example, 150-440°C, 180-350°C, or 200-300°C may be used.
[0030] The thermoplastic composition may comprise at least one polymer, for example, at least two different polymers, at least three different polymers, at least four different polymers, etc. The polymer may be any polymer selected from the group of thermoplastic polymers or a combination of different thermoplastic polymers. The polymer may be selected from one or more of the following: polyethylene, polypropylene, polystyrene, ethylene-vinyl acetate (EVA), polybutylene adipate terephthalate (PBAT), polyamide, polyacrylate, polyester, acrylonitrile butadiene styrene (ABS), polycarbonate, polylactic acid (PLA), polyvinyl chloride (PVC), etc. In one embodiment, the polymer is selected from polypropylene and / or polystyrene. That is, to produce a flame-retardant thermoplastic composition, one type of polymer may be used or a combination of two or more different polymers may be used.
[0031] In this specification, the expression “lignin-based filler” should be understood to refer to a filler prepared from hydrothermal carbonized (HTC) lignin material unless otherwise specified.
[0032] Hydrothermal carbonization (HTC) treatment is also known as "aqueous carbonization at elevated temperature and pressure." Hydrothermal carbonization of lignin refers to the thermochemical conversion process of lignin-containing materials in an aqueous suspension. Hydrothermal carbonization of lignin produces lignin derivatives with high carbon content and functional groups. Therefore, it is a chemical process that converts organic compounds into structured carbon.
[0033] The lignin material used to manufacture lignin-based fillers may be selected from the group consisting of kraft lignin, steam explosion lignin, biorefinery lignin, supercritical separation lignin, hydrolysis lignin, flash precipitated lignin, biomass originating lignin, lignin from alkaline pulping process, lignin from soda process, lignin from organosolv pulping, lignin from alkali process, lignin from enzymatic hydrolysis process, and any combination thereof. In one embodiment, the lignin is wood-based lignin. Lignin can originate from softwood, hardwood, annual plants, or any combination thereof.
[0034] In this specification, "Kraft lignin" should be understood as lignin derived from Kraft black liquor unless otherwise specified. Black liquor is an alkaline aqueous solution of lignin residue, hemicellulose, and inorganic chemicals used in the Kraft pulping process. The black liquor produced during the pulping process contains components derived from different softwood and hardwood species in varying proportions. Lignin can be separated from black liquor through different techniques, such as precipitation and filtration. Lignin typically begins to precipitate at pH values below 11–12. Different pH values may be used to precipitate lignin fractions with different characteristics. These lignin fractions differ from one another based on molecular weight distribution, e.g., Mw and Mn, polydispersity, hemicellulose, and extract contents. The molar mass of lignin precipitated at higher pH values is higher than the molar mass of lignin precipitated at lower pH values. Furthermore, the molecular weight distribution of the lignin fraction precipitated at lower pH values is broader than that of the lignin fraction precipitated at higher pH values. The precipitated lignin can be purified from inorganic impurities, hemicellulose, and wood extracts through an acidic washing step. Further purification is possible through filtration.
[0035] In this specification, the term "flash-precipitated lignin" should be understood as lignin precipitated from black liquor in a continuous process by using a carbon dioxide-based acidifying agent, preferably carbon dioxide, under the influence of an overpressure of 200–1000 kPa to lower the pH of the black liquor flow to a lignin precipitation level and abruptly releasing the pressure for lignin precipitation. A method for producing flash-precipitated lignin is disclosed in patent application FI 20106073. The retention time of the method is less than 300 seconds. Flash-precipitated lignin particles with a particle diameter of less than 2 μm form clumps, which can be separated from the black liquor, for example, by filtration. An advantage of flash-precipitated lignin is its higher reactivity compared to ordinary kraft lignin. Flash-precipitated lignin can be purified and / or activated as needed for further processing.
[0036] Lignin can originate from an alkaline process. The alkaline process may begin by liquefying biomass using a strong alkali, followed by a neutralization process. After alkaline treatment, lignin may precipitate in a manner similar to that presented above.
[0037] Lignin can be derived from steam blasting. Steam blasting is a pulping and extraction technology that can be applied to wood and other fibrous organic materials.
[0038] In this specification, "biorefinery lignin" should be understood as lignin that can be recovered from refining facilities or processes in which biomass is converted into fuel, chemicals, and other substances, unless otherwise specified.
[0039] In this specification, "supercritical separation lignin" should be understood as lignin that can be recovered from biomass using supercritical fluid separation or extraction techniques, unless otherwise specified. Supercritical conditions correspond to temperatures and pressures above the critical point of a given substance. Under supercritical conditions, there are no distinct liquid and gaseous phases. Supercritical water or supercritical liquid extraction is a method of using water or a liquid under supercritical conditions to decompose biomass and convert it into cellulosic sugars. The water or liquid acting as a solvent extracts sugars from the cellulosic plant material, while the lignin remains as solid particles.
[0040] Lignin can originate from hydrolysis processes. Lignin derived from hydrolysis processes can be recovered from paper pulp or wood chemical processes.
[0041] Lignin can be derived from the organosolv process. Organosolv is a pulping technology that uses organic solvents to dissolve lignin and hemicellulose.
[0042] In one embodiment, the lignin-based filler is prepared from lignin material derived from an enzymatic hydrolysis process and / or a Kraft process and is hydrothermally carbonized. In one embodiment, the lignin-based filler is prepared from lignin material derived from an enzymatic hydrolysis process and is hydrothermally carbonized. In one embodiment, the lignin-based filler is prepared from lignin material derived from a Kraft process and is hydrothermally carbonized.
[0043] In one embodiment, the starting material for manufacturing the lignin-based filler is lignin material obtained from an enzymatic hydrolysis process. In one embodiment, enzymatic hydrolysis involves the enzymatic hydrolysis of a plant-based feedstock, such as a wood-based feedstock. In one embodiment, enzymatic hydrolysis involves the enzymatic hydrolysis of cellulose. Enzymatic hydrolysis is a process in which enzyme(s) help to cleave molecular bonds by adding water elements. In one embodiment, enzymatic hydrolysis involves the enzymatic hydrolysis of cellulose. In one embodiment, the lignin-based filler is manufactured from lignin material derived from an enzymatic hydrolysis process that has been hydrothermally carbonized.
[0044] In one embodiment, the lignin-based filler is prepared from lignin derived from the pulping of wood, for example, kraft lignin.
[0045] Lignin-based fillers as disclosed in this specification may be prepared as disclosed below. The lignin used may be derived from a process in which, for example, lignin is formed from the enzymatic hydrolysis of a lignocellulose feedstock or lignin is derived from a Kraft process. Additionally, other lignin sources as disclosed in this specification may also be used.
[0046] The derived lignin material can be dissolved in an alkaline solution such as NaOH. Dissolution can be achieved by heating the mixture of lignin and the alkaline solution to approximately 80°C, adjusting the pH to a value higher than 7 (such as 9–11), and mixing the mixture of lignin and the alkaline solution for a predetermined period of time. The mixing time may continue for approximately 2–3 hours. The precise pH value is determined according to the product grade target.
[0047] Subsequently, the dissolved lignin material can be hydrothermal carbonization (HTC).
[0048] Hydrothermal carbonization treatment can be performed in a reactor (HTC reactor) or, if necessary, in a batch manner in multiple parallel reactors. The dissolved lignin material may be preheated before entering the HTC reactor(s). The temperature of the HTC reactor(s) may be 150-250°C and the pressure may be 20-30 bar. The residence time in the HTC reactor(s) may be about 3 to 6 hours. In the HTC reactor, as the lignin is carbonized, a stabilized lignin derivative with a large specific surface area may precipitate. Subsequently, the formed slurry containing the carbonized lignin may be removed and cooled. As a result, a slurry containing a lignin-based filler is formed.
[0049] A slurry containing a lignin-based filler can be fed to a separation device, and the precipitated lignin can be separated from the slurry. The separated lignin-based filler can be dried and recovered. The lignin-based filler can be washed before drying if necessary. The crushed lignin particles can be dried and used as a lignin-based filler.
[0050] In the process described above, lignin polymers are linked together. Therefore, lignin-based fillers can be considered to contain or consist of linked lignin polymers. Linked or connected lignin polymers may no longer be soluble. However, since smaller lignin polymer chains still remain soluble, standard analytical techniques such as size exclusion chromatography or nuclear magnetic resonance spectroscopy (NMR spectroscopy) can be applied, which requires dissolving the analyte in a solvent. Thus, different characteristics of the soluble fraction of the lignin-based filler can be determined.
[0051] In one embodiment, the lignin-based filler contains ash in a total amount of 0.1-3 wt%, 0.1-2.5 wt%, 0.2-2.0 wt%, 0.3-1.5 wt%, or 0.4-1.0 wt%. The ash content can be measured according to the standard DIN 51719.
[0052] The inventors have surprisingly discovered that, for example, when lignin material obtained through an enzymatic hydrolysis process is used to produce lignin-based fillers, the ash content of the lignin-based fillers can be reduced. A lower ash content has the additional benefit of, for example, increasing the purity of the lignin-based fillers.
[0053] Lignin-based fillers may contain carbon in a total amount of 62-70% by weight. In one embodiment, the lignin-based filler contains carbon in a total amount of 63-69% by weight or 64-68% by weight. The carbon content in the lignin-based filler can be measured according to the standard DIN 51732 (1997). The inventors have surprisingly discovered that the amount of carbon in the lignin-based filler has additional utility in having a beneficial effect on the flame resistance of the thermoplastic composition compared to other lignin-containing fillers having a smaller amount of carbon. Thus, the amount of carbon in the lignin-based filler can help prevent combustion from occurring.
[0054] In one embodiment, the solubility of the lignin-based filler in 0.1 M NaOH is 1-40 wt%, 3-35 wt%, or 5-30 wt%. Solubility can be measured in the following manner: First, the sample is dried at a temperature of 60°C for 4 hours. A mass of 0.5 g of the sample is weighed and suspended in 50 ml of 0.1 M NaOH at a temperature of 22°C and a concentration of 1%. Mixing is continued for 1 hour, the sample is placed on glass microfiber paper (1.6 μm), and the filter paper containing the sample is dried at a temperature of 60°C for 2 hours. The dissolved portion of the sample can be measured by gravimetric measurement.
[0055] In one embodiment, the lignin-based filler has a weight-average molecular weight (Mw) of 1000–4000 Da, 1300–3700 Da, 1700–3200 Da, 2500–3000 Da, 2600–2900 Da, or 2650–2850 Da when measured based on the soluble fraction of the lignin-based filler. The weight-average molecular weight can be measured by size exclusion chromatography (SEC) using 0.1 M NaOH as the eluent and a sample volume of about 1 mg / ml dissolved in 0.1 M NaOH. The molecular weight is measured relative to a polystyrene sulfonate standard. A UV detector with a wavelength of 280 nm is used.
[0056] The polydispersity index (PDI) of lignin-based fillers can be 1.5–5.0, 1.8–4.5, 1.9–4.3, 2.1–4.0, 2.4–3.5, or 2.6–3.2 when measured based on the soluble fraction of the lignin-based filler. The polydispersity index can be measured by size exclusion chromatography (SEC). The PDI is a measure of the molecular mass distribution of a given polymer sample. The PDI is calculated by dividing the weight-average molecular weight (Mw) by the number-average molecular weight (Mn). The PDI represents the distribution of individual molecular masses in a polymer batch.
[0057] The STSA values of lignin-based fillers can be 3-150 m² / g, 5-100 m² / g, or 7-60 m² / g. STSA values can be measured according to the standard ASTM D6556.
[0058] In one embodiment, the lignin-based filler has a density of up to 1.5 g / cm³. In one embodiment, the lignin-based filler has a density of 1.0-1.5 g / cm³, 1.15-1.35 g / cm³, or 1.1-1.4 g / cm³. Density can be measured according to the standard ISO 21687.
[0059] The flame-retardant thermoplastic composition as disclosed herein has the additional utility of exhibiting improved fire resistance. Accordingly, the thermoplastic composition has the additional utility of being thermally stable. The inventors have surprisingly discovered that the lignin-based filler has a carbon content that has a beneficial effect on the ability of the thermoplastic composition to resist combustion.
[0060] The flame-retardant thermoplastic composition disclosed in this specification has the additional utility of exhibiting superior stability compared to, for example, a composition prepared using carbon black as a filler.
[0061] Examples
[0062] Now, various embodiments will be referred to in detail.
[0063] The following description discloses some embodiments in sufficient detail to enable a person skilled in the art to utilize the embodiments based on the present disclosure. Not all steps or features of the embodiments are discussed in detail, as many steps or features will be apparent to a person skilled in the art based on the present specification.
[0064] Example 1 - Flame resistance test of a thermoplastic composition
[0065] The purpose of the present embodiment was to evaluate the flammability of a flammable thermoplastic composition by comparing it with the flammability of a corresponding thermoplastic composition. As noted above, the corresponding thermoplastic composition was prepared in a manner similar to that of the flammable thermoplastic composition, but the lignin material was not hydrothermally carbonized during the preparation of the lignin-based filler. The filler used in the corresponding thermoplastic composition is referred to as pristine lignin in this embodiment.
[0066] As a comparative example, a native thermoplastic composition containing no filler and a thermoplastic composition using carbon black as a filler were also prepared.
[0067] The lignin-based filler was prepared according to the description provided above in this specification using lignin material generated during the enzymatic hydrolysis process and subjected to hydrothermal carbonization. The pure lignin was lignin obtained from the same enzymatic hydrolysis process as wood but not subjected to hydrothermal carbonization. The carbon black used was MONARCH®800 provided by Cabot. The characteristics of the lignin-based filler and pure lignin were measured and are shown in Table 1 below.
[0068] [Table 1]
[0069]
[0070] The carbon content of the carbon black was > 95% and the density was 1.8 g / cm³.
[0071] First, the following thermoplastic composition was prepared:
[0072] [Table 2]
[0073]
[0074] The thermoplastic composition was prepared by combining the following components at a processing temperature suitable for each polymer type: 40 wt% filler, 52 wt% polymer, and a total of 8 wt% additive package (consisting of 2% Ca-stearate (lubricant), 2% Irganox 1010 antioxidant, and 4% polyethylene wax (lubricant)).
[0075] Three kg of each type of thermoplastic composition was prepared with a filler loading of 40 wt%. Combustion behavior was tested based on the horizontal combustion test ISO 3795:1989. The test was performed on molded masterbatches of PP and PS and their unfilled counterparts (comparative examples). The results of the combustion test are shown in the table below:
[0076] [Table 3]
[0077]
[0078] From the test results, it can be seen that the combustion behavior of the flame-retardant thermoplastic composition is significantly superior to that of the corresponding thermoplastic composition. The above results are somewhat similar to those of a thermoplastic composition in which carbon black is used as a filler.
[0079] It is obvious to those skilled in the art that the basic concept can be implemented in various ways as technology advances. Accordingly, embodiments are not limited to the embodiments described above; instead, they may vary within the scope of the claims.
[0080] The embodiments described above may be used in any combination with one another. Some embodiments may be combined together to form additional embodiments. The thermoplastic compositions, uses, or methods disclosed herein may include at least one of the embodiments described above. It will be understood that the benefits and advantages described above may relate to one embodiment or to multiple embodiments. Embodiments are not limited to embodiments that solve some or all of the problems mentioned or embodiments that have some or all of the benefits and advantages mentioned. Also, references to "one" item will be understood to refer to one or more such items. In this specification, the term "comprising" is used to mean including the following feature(s) or act(s) without excluding the presence of one or more additional features or acts.
Claims
Claim 1 A burning-resistant thermoplastic composition comprising at least one polymer and a lignin-based filler, wherein the lignin-based filler is prepared from a hydrothermal carbonization treated lignin material, the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight, the burning rate of the burning-resistant thermoplastic composition is at least 20% lower than the burning rate of a corresponding thermoplastic composition, and the corresponding thermoplastic composition is prepared in a manner similar to the burning-resistant thermoplastic composition, but the lignin material used to prepare the lignin-based filler is not hydrothermal carbonized. Claim 2 A flame-retardant thermoplastic composition according to claim 1, wherein the combustion rate of the flame-retardant thermoplastic composition is at least 30%, at least 40%, at least 50%, or at least 60% lower than the combustion rate of the corresponding thermoplastic composition. Claim 3 A flame-retardant thermoplastic composition according to claim 1, comprising a lignin-based filler in a total amount of 0.1-60% by weight, 0.5-50% by weight, or 1-45% by weight based on the total weight of the flame-retardant thermoplastic composition. Claim 4 A flame-retardant thermoplastic composition according to claim 1, wherein the lignin material used to manufacture the lignin-based filler is derived from an enzymatic hydrolysis process and / or a Kraft process. Claim 5 A flame-retardant thermoplastic composition according to claim 1, wherein the lignin-based filler comprises ash in a total amount of 0.1-2.5 wt%, 0.2-2.0 wt%, 0.3-1.5 wt%, or 0.4-1.0 wt%. Claim 6 A flame-retardant thermoplastic composition according to claim 1, wherein the solubility of a lignin-based filler in 0.1M NaOH is 1-40 wt%, 3-35 wt%, or 5-30 wt%. Claim 7 A flame-retardant thermoplastic composition according to claim 1, wherein the weight average molecular weight (Mw) of the lignin-based filler is 1000-4000 Da, 1300-3700 Da, 1700-3200 Da, 2500-3000 Da, 2600-2900 Da, or 2650-2850 Da when measured based on the soluble fraction of the lignin-based filler. Claim 8 A flame-retardant thermoplastic composition according to claim 1, wherein the polydispersity index of the lignin-based filler is 1.5-5.0, 1.8-4.5, 1.9-4.3, 2.1-4.0, 2.4-3.5, or 2.6-3.2 when measured based on the soluble fraction of the lignin-based filler. Claim 9 A flame-retardant thermoplastic composition according to claim 1, wherein the lignin-based filler has an STSA value of 3-150 m² / g, 5-100 m² / g, or 7-60 m² / g. Claim 10 A composition comprising a lignin-based filler for use in improving the flame resistance of a thermoplastic composition comprising at least one polymer and a lignin-based filler, wherein the lignin-based filler is prepared from a hydrothermal carbonized lignin material, the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight, the combustion rate of the flame-resistant thermoplastic composition is at least 20% lower than the combustion rate of a corresponding thermoplastic composition, and the corresponding thermoplastic composition is prepared in a manner similar to that of the flame-resistant thermoplastic composition, but the lignin material used to prepare the lignin-based filler is not hydrothermal carbonized. Claim 11 A composition according to claim 10, wherein the combustion rate of the flame-retardant thermoplastic composition is at least 30%, at least 40%, at least 50%, or at least 60% lower than the combustion rate of the corresponding thermoplastic composition. Claim 12 A composition according to claim 10 or 11, wherein the flame-retardant thermoplastic composition comprises a lignin-based filler in a total amount of 0.1-60% by weight, 0.5-50% by weight, or 1-45% by weight, based on the total weight of the flame-retardant thermoplastic composition. Claim 13 A composition according to claim 10 or 11 in which the lignin material used to manufacture the lignin-based filler is derived from an enzymatic hydrolysis process and / or a Kraft process. Claim 14 A composition according to claim 10 or 11, wherein the lignin-based filler comprises ash in a total amount of 0.1-2.5 wt%, 0.2-2.0 wt%, 0.3-1.5 wt%, or 0.4-1.0 wt%. Claim 15 A composition according to claim 10 or 11, wherein the solubility of the lignin-based filler in 0.1M NaOH is 1-40 wt%, 3-35 wt%, or 5-30 wt%. Claim 16 A composition according to claim 10 or 11, wherein the weight average molecular weight (Mw) of the lignin-based filler is 1000-4000 Da, 1300-3700 Da, 1700-3200 Da, 2500-3000 Da, 2600-2900 Da, or 2650-2850 Da when measured based on the soluble fraction of the lignin-based filler. Claim 17 A composition according to claim 10 or 11, wherein the polydispersity index of the lignin-based filler is 1.5-5.0, 1.8-4.5, 1.9-4.3, 2.1-4.0, 2.4-3.5, or 2.6-3.2 when measured based on the soluble fraction of the lignin-based filler. Claim 18 A composition according to claim 10 or 11, wherein the lignin-based filler has an STSA value of 3-150 m² / g, 5-100 m² / g, or 7-60 m² / g. Claim 19 A method for producing a combustion-resistant thermoplastic composition comprising at least one polymer and a lignin-based filler, comprising the following steps: - providing at least one polymer and a lignin-based filler, wherein the lignin-based filler is prepared from a hydrothermal carbonized lignin material, and the lignin-based filler contains carbon in a total amount of 62-70% by weight and ash in a total amount of up to 3% by weight; and - combining at least one polymer and a lignin-based filler to form a combustion-resistant thermoplastic composition, wherein the combustion rate of the combustion-resistant thermoplastic composition is at least 20% lower than the combustion rate of a corresponding thermoplastic composition, and said corresponding thermoplastic composition is prepared in a manner similar to that of the combustion-resistant thermoplastic composition, but the lignin material used to prepare the lignin-based filler is not hydrothermal carbonized. Claim 20 A method according to claim 19, wherein the step of combining at least one polymer and a lignin-based filler comprises combining at least one polymer, a lignin-based filler and an additive, and molding the formed flame-retardant thermoplastic composition. Claim 21 An article comprising a flame-retardant thermoplastic composition according to any one of claims 1 to 9. Claim 22 Article of claim 21, wherein the thermoplastic composition is formed into an article by extrusion, injection molding, compression molding, blow molding, injection blow molding, injection stretch blow molding, thermoforming, vacuum forming, melt spinning, electrospinning, melt blowing, film blowing, film casting, extrusion coating, rotational molding, coextrusion, laminating, calendering, fused deposition modeling, or any combination thereof. Claim 23 A flame-retardant thermoplastic composition for use in packaging, housing, automotive parts, aviation parts, marine parts, machine parts, sports equipment, sports equipment parts, leisure equipment, leisure equipment parts, tools, tool parts, pipes, membranes, tubes, fittings, bottles, films, bags, sacks, textiles, ropes, containers, tanks, electrical components, electronic components, parts for energy generation, toys, home appliances, kitchenware, tableware, flooring, fabrics, medical applications, food contact materials, building materials, drinking water applications, or furniture, in any one of claims 1 to 9.
Citation Information
Patent Citations
Lignin-based flame retardant composition and preparation process thereof
JP2020534379A
Flame retardant resin composition and molded product
KR1020130130850A
Particulate carbon material that can be produced from renewable raw materials and method for the production of said carbon material
KR1020180083932A